The character strengths of class clowns - Ruch, Willibald; Platt, Tracey; Hofmann, Jennifer (Frontiers in Psychology, 2014)
Class clowns traditionally were studied as a type concept and identified via sociometric procedures. In the present study a variable-centered approach was favored and class clown behaviors were studied in the context of character strengths, orientations to happiness and satisfaction with life. A sample of 672 Swiss children and adolescents filled in an 18 item self-report instrument depicting class clown behaviors. A hierarchical model of class clown behaviors was developed distinguishing a general factor and the four positively correlated dimensions of “identified as a class clown,” “comic talent,” “disruptive rule-breaker,” and “subversive joker.” Analysis of the general factor showed that class clowns were primarily male, and tended to be seen as class clowns by the teacher. Analyses of the 24 character strengths of the VIA-Youth (Park & Peterson, 2006) showed that class clowns were high in humor and leadership, and low in strengths like prudence, self-regulation, modesty, honesty, fairness, perseverance, and love of learning. An inspection of signature strengths revealed that 75% of class clowns had humor as a signature strength. Furthermore, generally class clown behaviors were shown by students indulging in a life of pleasure, but low life of engagement. The four dimensions yielded different character strengths profiles. While all dimensions of class clowns behaviors were low in temperance strengths, the factors “identified as the class clown” and “comic talent” were correlated with leadership strengths and the two negative factors (“disruptive rule-breaker”, “subversive joker”) were low in other directed strengths. The disruptive rule breaking class clown was additionally low in intellectual strengths. While humor predicted life satisfaction, class clowning tended to go along with diminished satisfaction with life. It is concluded that different types of class clowns need to be kept apart and need different attention by teachers.